2002
DOI: 10.1073/pnas.132060599
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structures of a chitinase complexed with natural product cyclopentapeptide inhibitors: Mimicry of carbohydrate substrate

Abstract: Over the past years, family 18 chitinases have been validated as potential targets for the design of drugs against human pathogens that contain or interact with chitin during their normal life cycles. Thus far, only one potent chitinase inhibitor has been described in detail, the pseudotrisaccharide allosamidin. Recently, however, two potent natural-product cyclopentapeptide chitinase inhibitors, argifin and argadin, were reported. Here, we describe highresolution crystal structures that reveal the details of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
84
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 41 publications
2
84
0
Order By: Relevance
“…The only other known high affinity inhibitors of family 18 chitinases are the naturally occurring cyclopentapeptides argadin (4) and argifin (23). Structural and enzymological analyses have shown that these peptides bind intimately to the active site of ChiB with affinities in the 10 nM (argadin) and 10 M (argifin) range (24).…”
mentioning
confidence: 99%
“…The only other known high affinity inhibitors of family 18 chitinases are the naturally occurring cyclopentapeptides argadin (4) and argifin (23). Structural and enzymological analyses have shown that these peptides bind intimately to the active site of ChiB with affinities in the 10 nM (argadin) and 10 M (argifin) range (24).…”
mentioning
confidence: 99%
“…Chitin is not found in humans but plays a key role in the life cycles of several classes of human pathogens, such as fungi (1), nematodes (2), protozoan parasites (3), and insects (4). Several chitinase inhibitors with biological activity have been identified, such as allosamidin (5), styloguanidines (6), and the cyclic peptides CI-4 (7-9), argifin (10), and argadin (11,12). Allosamidin (see Fig.…”
mentioning
confidence: 99%
“…Although few specific NAGase inhibitors have been described, two potent NAGase inhibitors are streptozotocin and O-(2-acetamido-2-deoxy-D-glucopyranosylidene)amino-N-phenylcarbamate (Horsch et al 1991, Konrad et al 2001. Endo-chitinase inhibitors such as allosamidin, argifin, argidin, cyclic dipeptides, and psammaplin A have been studied to evaluate the toxic effects (via topical application and feeding bioassays) in insects-arthropods, including the parasitic blow fly (Lucile cuprina Wiedemann), southern cattle tick (Boophilus microplus Canestrini ), silkworm (Bombyx mori L.), webbing clothes moth (Tineola bisselliella Hummel), the American cockroach (Periplaneta americana L.), the German cockroach (Blattella germanica L.), and the green peach aphid or peach-potato aphid (Myzus persicae Sulzer) (Sakuda et al 1987, Londershausen et al 1996, Blattner et al 1997, Houston et al 2002, Saguez et al 2006, Huang 2012. However, production costs and availability make these chemicals impractical for implementation into an insecticide baiting program.…”
mentioning
confidence: 99%